Chia Seed(Saliviahispanica) – An Antioxidant Potent to Pharmacological Activities (International Journal of Scientific Research and Management (IJSRM), 2017)
Antioxidant is a substance that reduces damage due to oxygen, that caused by free radicals. The recent research focuses on searching the natural sources of antioxidant and the synthetic antioxidant are restricted due to their carcinogenicity. Chia (Saliviahispanica) are versatile herb as well as spice, and the seeds are shine due to their high amount of antioxidant that help to protect delegate fats in the seed. In the present study, the mucilage extraction of chia seed was prepared by method of Box-Behnn experimental design and the qualitative chemical tests carried out for the identification of the nature of phyto-constituents present in chia. Free radical scavenging activity and metal chelating activity were identified and it includes Total Flavonoid Content (TFC), Total Phenolic Content (TPC), DPPH and Total Antioxidant Content (TAC) was analyzed. The total antioxidant activity was performed according to Ferrick Thiocyanate method. At the 50µg/ml concentration of chia were found to be 0.28µg/ml of phenolic, 1.23mg of orientin, 2.78mg of vicenin, 1.7mg of vitamin C respectively. The chia had effective total antioxidant activity, DPPH radical scavenging, reducing power and metal chelating activities. Chia is good antioxidant potential with enlightened total phenolic and flavonoid content in management of cholesterol reduction and heart protection. The common dosage recommendation is 20gm of chia seed per day. Based on this properties, the present study was undertaken in such a way to utilize and explore the health benefits.